Women's perceived susceptibility to and utilisation of cervical cancer screening services in Malawi - Melanie Y. Hami; Valerie J. Ehlers; Dirk M. van der Wal (AOSIS, 2014)
Background: Malawi provides cervical cancer screening services free of charge at some public health facilities. Few women make use of these cancer screening services in Malawi and many women continue to be diagnosed with cervical cancer only during the late inoperable stages of the condition. Objectives: The purpose of this study was to discover whether the perceived susceptibility to cervical cancer, amongst Malawian women aged 42 and older, influenced their intentions to utilise the available free cervical cancer screening services. Method: A quantitative, cross-sectional descriptive study design was adopted. Structured interviews were conducted with 381 women who visited 3 health centres in the Blantyre District of Malawi. Results: A statistically-significant association existed between women's intentions to be screened for cervical cancer and their knowledge about cervical cancer (X² = 8.9; df = 1; p = 0.003) and with having heard about HPV infection (X² = 4.2; df = 1; p = 0.041) at the 5% significance level. Cervical cancer screening services are provided free of charge in government health institutions in Malawi. Nevertheless, low perceived susceptibility to cervical cancer amongst women, aged 42 and older, might contribute to limited utilisation of cervical screening services, explaining why 80% of cervical cancer patients in Malawi were diagnosed during the late inoperable stages. Conclusion: Malawian women lacked awareness regarding their susceptibility to cervical cancer and required information about the available cervical cancer screening services. Malawi's women, aged 42 and older, must be informed about the advantages of cervical cancer screening and about the importance of effective treatment if an early diagnosis has been made. Women aged 42 and older rarely attend antenatal, post-natal, well baby or family-planning clinics, where health education about cervical cancer screening is often provided. Consequently, these women aged 42 and older should be informed about cervical screening tests when they utilise any health services.